Effect of Rocking Movements on Afternoon Sleep - van Sluijs, Rachel M.; Rondei, Quincy J.; Schluep, Diana; Jäger, Lukas; Riener, Robert; Achermann, Peter; Wilhelm, Elisabeth (Frontiers in Neuroscience, 2020)
Study objectives Gentle rocking movements provided by a moving bed have been proposed as a promising non-pharmacological way to promote sleep. In rodents the sleep promoting effect of rocking movements depended on the peak acceleration (named “stimulation intensity”) perceived by the vestibular system. We set out to verify previous reports on the sleep promoting effect of rocking movements and to investigate the importance of stimulation intensity in this process. Methods Side-to-side rocking movements along a pendulum trajectory with different peak accelerations (baseline: 0 m/s2, low intensity: 0.15 m/s2, medium intensity: 0.25 m/s2, high intensity: 0.35 m/s2) were provided for 45 min during an afternoon nap opportunity. Participants were assigned to a low intensity group (n = 10) experiencing baseline, low and medium intensity stimulation or a high intensity group (n = 12) experiencing baseline, medium and high intensity stimulation. Sleep and sleep-related memory performance were assessed using polysomnography and a word-pair memory task, respectively. Results Participants transitioned faster into deep sleep under the influence of medium intensity rocking as was evident by a faster buildup of delta power compared to baseline (n = 22). Previously reported effects like a shorter latency to stage N2 and a higher density of sleep spindles were not observed. Sleep quality during baseline naps of the low intensity group was worse than in the high intensity group. In the low intensity group, we also observed a significant increase in delta power throughout the nap, as well as a higher density of slow oscillations both under the influence of low and medium intensity vestibular stimulation. No such effects were observed in the high intensity group. Conclusion Rocking movements may promote nap sleep in young adults. Due to a difference in sleep quality during baseline naps between the low and high intensity group no conclusion regarding the influence of stimulation intensity were possible. Thus, optimal stimulation settings in humans need further investigation.